2021
DOI: 10.1002/jclp.23210
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the relationship between continuing bonds and adjustment after the death of a first‐degree family member by using the Multidimensional Continuing Bonds Scale

Abstract: Objectives The study aims to develop a continuing bonds scale, investigate the relationship between continuing bonds and adjustment after loss, and test the moderating role of meaning reconstruction in this relationship. Methods Data were collected from two different samples of 306 (Study 1) and 271 (Study 2) bereaved adults. Results The four factors structure of the Multidimensional Continuing Bonds Scale (MCBS) was explored and confirmed. Hierarchical regression analysis revealed that continuing bonds showed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 40 publications
(66 reference statements)
1
0
0
Order By: Relevance
“…It is possible that the death of a family member in a traffic accident (often perceived as a preventable death) elevates adverse emotions in the mourners which reframe the memories of the pre-death relationship (Levi-Belz, 2017). Moreover, as in previous research (Keser & Işıklı, 2021), the study findings emphasize the importance of active relational grieving, as it was found to be associated with psychological distress for all of the mourner groups.…”
Section: Discussionsupporting
confidence: 87%
“…It is possible that the death of a family member in a traffic accident (often perceived as a preventable death) elevates adverse emotions in the mourners which reframe the memories of the pre-death relationship (Levi-Belz, 2017). Moreover, as in previous research (Keser & Işıklı, 2021), the study findings emphasize the importance of active relational grieving, as it was found to be associated with psychological distress for all of the mourner groups.…”
Section: Discussionsupporting
confidence: 87%
“…Tanto la CV interna como la CV externa han sido sugeridas como predictores de mayor intensidad en el duelo, pero sería delicado pronosticar el oficio de la CV en el proceso de duelo ya que la vehemencia de la experiencia podría relatar la relación existente antes de la muerte, desencadenando un esfuerzo mayor por mantenerla 23 . Pese a ello, se han evidenciado correlaciones positivas de CV con duelo complicado, y de CV con crecimiento personal tanto en hombres como en mujeres 4,24 .…”
Section: Discussionunclassified